1994
DOI: 10.1128/jb.176.20.6324-6333.1994
|View full text |Cite
|
Sign up to set email alerts
|

The accumulation of glutamate is necessary for optimal growth of Salmonella typhimurium in media of high osmolality but not induction of the proU operon

Abstract: Synthesis of glutamate can be limited in bacterial strains carrying mutations to loss of function of glutamate synthase (2-oxoglutarate.glutamine aminotransferase) by using low concentrations of NH4' in the growth medium. By using such gtBID mutant strains of Sabnonella typhimnurum, we demonstrated that: (i) a large glutamate pool, previously observed to correlate with growth at high external osmolality, is actually required for optimal growth under these conditions; (ii) the osmoprotectant glycine betaine (NN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
90
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 46 publications
4
90
1
Order By: Relevance
“…The proU operon (encoding a transport system for proline and glycine betaine) promoter is induced by low water potential in Escherichia coli and Salmonella (Wright & Beattie, 2004). Similarly, glutamate has also been shown to be necessary for S. Typhimurium to grow optimally in a highosmolarity environment (Csonka et al, 1994). We insertionally inactivated the amino acid transporter genes (SEN1417-1420) in a PT4 strain and confirmed the mutation by thorough PCR and CGH analysis.…”
Section: Discussionmentioning
confidence: 92%
“…The proU operon (encoding a transport system for proline and glycine betaine) promoter is induced by low water potential in Escherichia coli and Salmonella (Wright & Beattie, 2004). Similarly, glutamate has also been shown to be necessary for S. Typhimurium to grow optimally in a highosmolarity environment (Csonka et al, 1994). We insertionally inactivated the amino acid transporter genes (SEN1417-1420) in a PT4 strain and confirmed the mutation by thorough PCR and CGH analysis.…”
Section: Discussionmentioning
confidence: 92%
“…Osmolyte pools were estimated using a standard curve for each compound with acetone as the internal standard. Intracellular pools are reported in nanomoles per milliliter per optical density at 550 nm [OD 550 ] unit as described by Csonka et al (14).…”
Section: Microorganismsmentioning
confidence: 99%
“…Glutamate is the most abundant free amino acid in the cytoplasm of E. coli and related organisms during aerobic growth in mineral salts media (14,27,33). In addition to essential roles in nitrogen assimilation and biosynthesis, glutamate also serves as a protective intracellular osmolyte during adaptation to osmotic stress (13-15, 32, 50).…”
mentioning
confidence: 99%
“…Csonka et al (13) 4 ϩ with L-aspartate or L-asparagine abolishes its osmosensitivity; and (iii) a multicopy plasmid which suppresses the gltBD defect in the mutant also confers osmotolerance. These data implicate a defect in N assimilation as the basis for the osmosensitive phenotype of GJ193 and provide additional evidence that increased L-glutamate synthesis and accumulation are important in E. coli osmoregulation (2,13,37).…”
Section: Discussionmentioning
confidence: 99%
“…Botsford et al (2) and McLaggan et al (37) have argued that the increase in L-glutamate pools in cultures grown at elevated osmolarity represents a very small, and possibly insignificant, load in comparison with the total biosynthetic flux through the amino acid. On the other hand, Csonka et al (13) have recently shown that, in GOGAT-defective mutants of S. typhimurium grown under ammonia-limiting conditions, there is an inverse relationship between growth rate and the osmolarity of the culture medium. The latter result provides indirect genetic evidence that increased L-glutamate synthesis is necessary for optimal growth under hyperosmotic stress.…”
mentioning
confidence: 99%